Dampak Setelah Terjadinya Bencana Alam Galodo Terhadap Masyarakat di Kabupaten Solok - Al-Ikhlas .; Ardiansyah Reza; Fournanda Chesa Apri; Tanjung Zulmayanti Arfat; Raflis Rima (CV. ITTC INDONESIA, 2026)
The Galodo disaster that occurred in Nagari Paninggahan, Solok Regency, had a significant impact on the lives of the community, especially the agricultural sector, which is the primary source of livelihood for residents. Damage to agricultural land, homes, and infrastructure led to a decline in the community's economic condition and hampered daily activities. However, amidst the various losses experienced, the community demonstrated a high level of solidarity and social concern through mutual cooperation activities, mutual assistance, and distribution of aid to affected residents. The involvement of KKN students in various recovery activities also helped strengthen social relations between the community and outsiders. Thus, the Galodo disaster not only had a negative impact on the economic aspect, but also became a momentum that strengthened social cohesion and the community's spirit of togetherness in facing and recovering from post-disaster conditions.